Exploration of the Defect Passivation in Perovskite Materials Using Organic Spacer Cations. Issue 10 (4th February 2022) - Shen, Kongchao; Wang, Jingkun; Lu, Yu; Shen, Yang; Li, Yan‐Qing; Su, Zhenhuang; Chen, Li; Song, Fei; Gao, Xingyu; Tang, Jian‐Xin
Abstract: Quasi‐2D metal halide perovskite light emitting diodes (PeLEDs) have attracted a lot of attentions in recent years, while their potential applications in displays and lighting are limited by the device stability. Although defect passivation in PeLEDs is an effective method to ameliorate the unstable problem, the underlying mechanisms need to be further explored. Herein, organic spacer cations with different charge distributions and formation energies in quasi‐2D CsPbBr3 perovskites are utilized to unravel the defect passivation mechanisms, including phenylmethanamine, 2‐phenylethanamine bromide, and 4‐phenylbutylammonium. The experimental findings and density functional theory calculation reveal that the defect passivation occurs by the electrostatic interaction between defective PbBr6 4− octahedrons and proper organic spacer cations during the annealing process, particularly at the grain boundaries. The thermal stability of the perovskite films and device performance are improved after the effective defect passivation process. The exploration of the defect passivation process in perovskites will be beneficial to the development of high‐performance PeLEDs. Abstract : The defect passivation mechanisms of quasi‐2D perovskites induced by organic spacer cations with different charge distributions and formation energies are unveiled by in situ characterizations and theoretical calculations. The crystallization process of perovskites with suppressed defect states can be affected due to electrostatic interaction between defective PbBr6 4− octahedrons and organic spacer cations at the grain boundaries.